The effect of heat-polymerized acrylic resin denture base immersion in mangosteen peel extract as denture cleanser on streptococcus mutans - Tri Oktaviani; Dewi Kristiana; Swasthi Prasetyarini (Journal of Dentomaxillofacial Science, 2021)
Objective: Tooth loss can be treated by using dentures. The denture that facing the mucosa is rough and poor porosity, an ideal place for the growth of microorganisms, one of which is Streptococcus mutans. Microorganism growth can be inhibited by cleaning dentures using denture cleansers which has antibacterial activity. One of the natural ingredients that have an antibacterial activity is mangosteen peel extract. This study aims to determine the effect of mangosteen peel extract 25%, 50%, 75%, and 100% as denture cleanser agents on the growth of S. Mutans bacteria. Material and Methods: This research is an experimental laboratory study . Thirty-six acrylic resin contaminated with S. mutans were divided into 6 groups and immersed for 6 hours in each group in sterile aquadest (K-), sodium hypochlorite (K+), mangosteen peel extract 25% , extract 50%, extract 75%, extract 100%. Then the concentration of bacteria was measured using a spectrophotometer. Results: The results showed the highest number of S. mutans in the sterile aquadest group and the least was 100% mangosteen peel extract but the difference was not too significant with 75% mangosteen peel extract. Conclusions: Mangosteen peel extract as denture cleanser can inhibit the growth of S. mutans bacteria. 75% mangosteen peel extract is most effective in reducing the amount of S. mutans. Further research needs to be done on the effectiveness of mangosteen peel extract on the growth of S. mutans bacteria on a heat cured acrylic resin with different variations of the immersion time. Keywords: acrylic resin, S. mutans, mangosteen peel extract